1998
DOI: 10.1046/j.1365-2672.1998.853567.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbial involvement in the elevation of copper levels in drinking water

Abstract: A study of bacterial populations in metropolitan Adelaide domestic reticulation pipes was conducted to investigate a possible link between copper in drinking water and biofilms. Biofilm densities from cold water copper pipes at 10 sample sites were measured by viable cell counts. The range detected was from <2 × 101 to 3·25 × 107 cfu cm−2. Five isolates were selected for further experiments as they represented a range of responses to solvated copper and relative tendency for adhesion on glass slides. Drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…2007), and biofilms in corroding copper pipes may be composed of different groups of micro‐organisms, as a spatial and chemical heterogeneity has been described in their surfaces (Keevil 2004). Microbial studies in copper plumbing corrosion biofilms has been addressed utilizing culture‐dependent methods (Dutkiewicz and Fallowfield 1998; Bremer et al. 2001; Critchley et al.…”
Section: Introductionmentioning
confidence: 99%
“…2007), and biofilms in corroding copper pipes may be composed of different groups of micro‐organisms, as a spatial and chemical heterogeneity has been described in their surfaces (Keevil 2004). Microbial studies in copper plumbing corrosion biofilms has been addressed utilizing culture‐dependent methods (Dutkiewicz and Fallowfield 1998; Bremer et al. 2001; Critchley et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, drinking water isolates of the genera Agrobacterium, Acidovorax, Sphingomonas, and Micrococcus have been reported to increase copper levels in drinking water pipes, with corrosion dependent on microbial activity (9,10,14,23,37). In other studies, Rhodococcus, Stenotrophomonas, and Xanthomonas have been shown to decrease copper levels by sorbing soluble copper in their exopolysaccharide (EPS) (2,28,47).…”
mentioning
confidence: 99%
“…To count the bacteria adhering to the test coupons, they were removed by scratching with a surgical knife as described by Dutkiewicz and Fallowfield [18] and inoculated in both media (Postgate B and R2A) and added with agar-agar (1.5%) as a gelling agent.…”
Section: Methodsmentioning
confidence: 99%